Analysis of the financial markets during the trade war between China and the United States - Salcedo - Mayorga, Jorge Mario (Universidad Francisco de Paula Santander, 2020)
This document aims to analyze the impact on the volatility of financial markets, product of the trade war waged by the United States and China, using DCC-MGARCH heteroscedastic models of dynamic correlation for 12 world stock indices (United States, Colombia, Brazil, Chile, Mexico, Peru, England, Germany, China, Japan, South Africa and China). The results confirm that the volatility of the 12 markets has increased during 2019, as a result of the announcements made by Donald Trump, regarding the imposition of tariffs on Chinese imported goods. On the other hand, it is observed that the degree of integration in stock market terms of the countries worldwide with respect to China (Shanghai Stock Exchange Composite Index) is relatively low, registering dynamic correlations between 0.20 and 0.40, values ​​that are far from the correlations against United States (S & P500), which fluctuate in a range between 0.30 and 0.60. Lastly, it can be detailed that although the volatility caused by the trade war affects the behavior of the stock indices, it does not manage to generate the records seen in the subprime crisis of 2008 or debt in Europe for 2011-2012.